Enhanced effect of the immunosuppressive soluble HLA-G2 homodimer by site-specific PEGylation - Chisato Yamada; Kimiko Kuroki; Naoyoshi Maeda; Hiroshi Watanabe; Ami Takahashi; Katsumi Maenaka (Scientific Reports)
Abstract Human leukocyte antigen (HLA)-G is a nonclassical HLA class I molecule that has an immunosuppressive effect mediated by binding to immune inhibitory leukocyte immunoglobulin-like receptors (LILR) B1 and LILRB2. A conventional HLA-G isoform, HLA-G1, forms a heterotrimeric complex composed of a heavy chain (α1-α3 domains), β2-microglobulin (β2m) and a cognate peptide. One of the other isoforms, HLA-G2, lacks a α2 domain or β2m to form a nondisulfide-linked homodimer, and its ectodomain specifically binds to LILRB2 expressed in human monocytes, macrophages, and dendritic cells. The administration of the ectodomain of HLA-G2, designated the soluble HLA-G2 homodimer, showed significant immunosuppressive effects in mouse models of rheumatoid arthritis and systemic lupus erythematosus, presumably by binding to a mouse ortholog of LILRB2, paired immunoglobulin-like receptor B. However, the refolded soluble HLA-G2 homodimer used in these studies tends to aggregate and degrade; thus, its stability for clinical use has been a concern. In the present study, we improved the stability of the refolded soluble HLA-G2 homodimer via a site-directed PEGylation method. PEGylation at an original free cysteine residue, Cys42, resulted in increased lyophilization and thermal and serum stability. Furthermore, the PEGylated soluble HLA-G2 homodimer could better suppress atopic symptoms in mice than the non-PEGylated homodimer. These results suggest that PEGylated soluble HLA-G2 homodimers could be candidates for immunosuppressive biologics that specifically target LILRB2-positive myelomonocytic antigen-presenting cells.